Pengaruh High-Intensity Interval Training dan Lower Body Strength Training terhadap Kecepatan Sprint Pemain Sepak Bola - Bramantyo Akbar Putu Wijaya; Kodrad Budiono; Pipit Fitria Yulianto (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to compare the effectiveness of High-Intensity Interval Training (HIIT) and Lower Body Strength Training (LBST) on 30-meter sprint speed in youth football players. Employing a pretest-posttest comparison group design, 30 players from R2 Solo Club (14.27±0.74 years) were divided into two groups (n = 15) through Matched Subject Ordinal Pairing. The 30-meter acceleration test instrument was used with high reliability (Cronbach’s α = 0.996). Data analysis included t-tests, Smallest Detectable Change (SDC), Minimal Important Difference (MID), and Cohen’s d. The results showed that both methods had a significant effect (p < 0.001). The HIIT group experienced an improvement of 0.320 seconds (6.78%), while LBST improved by 0.127 seconds (2.67%). Clinically, the improvements in both groups exceeded the SDCgroup (0.02 seconds) and MID (0.026 seconds) thresholds. However, HIIT proved to be significantly superior to LBST (p < 0.001) with an improvement margin 0.193 seconds (4.11%) greater. The effect size values for the HIIT group (d = 3.833), the LBST group (d = 3.215), and the comparison between groups (d = 2.961) were all categorized as very large. It is concluded that HIIT provides a significantly greater performance acceleration than LBST. Coaches are advised to prioritize HIIT for accelerative speed improvement while maintaining LBST as a foundation for the players’ structural stability.